Tourism exhibitionism of a socialist destination - Rangus, Marjetka (Teorija in praksa, 2014)
In this article we propose a new approach to exploring the political system of socialist Yugoslavia. Using interdisciplinary methods of research, both political science and tourism enable us to understand better our present and past social environment in a specific historical moment, i.e. the period from 1945 to 1991. We argue that by borrowing some of the concepts from tourism we can shed new light on the specifics of Yugoslavia's socialist political systems. In this article we use tourism theory to explain the positioning and self-perception of Yugoslavia's socialist self-management assembly system by its leading politicians.
Keywords: Jugoslavija; Parlamentarizem; Parliamentarism; Socialism; Socializem; Sociologija turizma; Sociology of tourism; Tourism; Turizem; Yugoslavia